SARS-CoV-2 Omicron Variant in Croatia—Rapid Detection of the First Case and Cross-Border Spread - Ferenčak, Ivana; Obrovac, Mihaela; Žmak, Ljiljana; Kuzle, Josipa; Petrović, Goranka; Vilibić-Čavlek, Tatjana; Jurić, Dragan; Jurić, Anita; Hruškar, Željka; Capak, Krunoslav; Stevanović, Vladimir; Milanović, Maja; et al. (Pathogens (Basel), 2022)
Background: Due to rapid spread, the Omicron variant has become the dominant SARS-CoV-2 variant responsible for infections worldwide. We present the first detection of the Omicron variant in Croatia which resulted in rapid cross-border spreading. Methods: Whole-genome sequencing was performed using the Illumina MiniSeq sequencing system. SARS-CoV-2 lineages were identified using the PANGOLIN and GISAID databases. Results: The first case of the Omicron variant (BA.1.17) emerged in Croatia after a workshop held in Zagreb in November 2021. The patient reported a history of previous COVID-19 and received two doses of an mRNA vaccine. Three additional cases were detected among Croatian participants of the workshop. At the beginning of December, SARS-CoV-2 infection was confirmed in one participant from Montenegro and her husband. Phylogenetic analysis showed that the detected Omicron variants were closely related to the first Croatian case, confirming the connection with the workshop outbreak and rapid cross-border spreading. Subsequent analyses of SARS-CoV-2 positive samples in Croatia showed the rapid introduction of the Omicron variant and depletion of the Delta variant resulting in the fifth pandemic wave. Conclusions: Genomic monitoring and early detection of novel SARS-CoV-2 variants are essential to implement timely epidemiological interventions and reduce further transmission in the population.